Insertion-related pain with intramedullary nailing. (June 2017) - Jang, Yohan; Kempton, Laurence B.; Mckinley, Todd O.; Sorkin, Anthony T.
Abstract: The use of intramedullary nails for the treatment of long bone fractures has become increasingly frequent over the last decade with gradually expanding indications and technological advances. Improved biomechanics relative to plates and less direct fracture exposure are some of the potential benefits of intramedullary nails. However, persistent insertion-related pain is common and may limit satisfactory long term outcomes. The etiologies of this phenomenon remain unclear. Proposed theories for which there is a growing body of supporting evidence include hardware prominence, suboptimal nail entry points leading to soft tissue irritation and structural compromise, local heterotrophic ossification, implant instability with persistent fracture micromotion, and poorly defined insertional strain. Many factors that lead to insertion-related pain are iatrogenic, and careful attention to detail and refined surgical techniques will optimize outcomes.